VALIDITY AND RELIABILITY STUDY OF THE TURKISH VERSION OF THE MEASURE OF ONLINE DISINHIBITION (MOD) - Çelik, Fatih; Savcı, Mustafa; Şahin, Yahya Şahin; Griffiths, Mark; Köse, Nihat (My University, 2025)
The present study examined the validity and reliability of the Turkish version of the Measure of Online Disinhibition (MOD), originally developed by Stuart and Scott (2021). Data were collected from Turkish university students from four different samples (Total N = 663; 74% female) comprising a (i) pilot study (Sample 1; N=35) to test the translation of the MOD, (ii) a study to test the factor structure of the Turkish MOD (Sample 2; N=284), (iii) study to assess the criterion validity of the Turkish MOD (Sample 3; N=289), and (iv) study to assess the test-retest reliability of the Turkish MOD (Sample N=55). Confirmatory factor analysis confirmed the unidimensional factor structure (?2/df=3.803, CFI=.91, RMSEA=.10, SRMR=.06). MOD scores were significantly positively associated with scale scores assessing online bullying (r = .19, p < .01), internet addiction (r = .38, p < .01), Machiavellianism (r = .29, p < .01), psychopathy (r = .21, p < .01), online histrionic personality (r = .54, p < .01), frequency of checking the internet (r = .19, p < .01), and frequency of checking social media (r = .12, p < .05). MOD scores were significantly negatively associated with life satisfaction (r = -.21, p < .01). Both alpha and omega coefficients of the MOD in Studies 2 and 3 were very good to excellent (ranging between .89 and .91). The test-retest reliability coefficient of the MOD was .78 (Study 4). Based on the findings, the MOD is a valid and reliable scale for assessing online disinhibition among Turkish-speaking individuals.
Keywords: Social Media Use; Internet Use; Online Disinhibition; Measure of Online Disinhibition.